Entrepreneurship Development and Business Ethics - T. Naga Lakshmi; Ch.Srinivas Reddy; Garima Agarwal; K.V.N. Sandhya; Susheela Kanduri (Mumbai HImalaya Publishing House, 2017)
All
Keywords: Management